2021
DOI: 10.1155/2021/6696198
|View full text |Cite
|
Sign up to set email alerts
|

Identified GNGT1 and NMU as Combined Diagnosis Biomarker of Non-Small-Cell Lung Cancer Utilizing Bioinformatics and Logistic Regression

Abstract: Non-small-cell lung cancer (NSCLC) is one of the most devastating diseases worldwide. The study is aimed at identifying reliable prognostic biomarkers and to improve understanding of cancer initiation and progression mechanisms. RNA-Seq data were downloaded from The Cancer Genome Atlas (TCGA) database. Subsequently, comprehensive bioinformatics analysis incorporating gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and the protein-protein interaction (PPI) network was conducted to identify d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 123 publications
0
19
0
1
Order By: Relevance
“…Transducin, also known as GMPase, mediates the activation of a cyclic GTP-specific (guanosine monophosphate) phosphodiesterase by rhodopsin. Zhang et al [ 53 ] reported that the expression level of GNGT1 in NSCLC was overexpressed, and the high expression of GNGT1 was significantly associated with worse OS in patients with NSCLC. NPSR1 is a G-protein-coupled receptor that induces intracellular signaling upon stimulation by neuropeptide S (NPS) via mobilization of calcium, increased cyclic adenosine monophospate (cAMP) levels, and activation of the mitogen-activated protein kinase (MAPK) pathway [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transducin, also known as GMPase, mediates the activation of a cyclic GTP-specific (guanosine monophosphate) phosphodiesterase by rhodopsin. Zhang et al [ 53 ] reported that the expression level of GNGT1 in NSCLC was overexpressed, and the high expression of GNGT1 was significantly associated with worse OS in patients with NSCLC. NPSR1 is a G-protein-coupled receptor that induces intracellular signaling upon stimulation by neuropeptide S (NPS) via mobilization of calcium, increased cyclic adenosine monophospate (cAMP) levels, and activation of the mitogen-activated protein kinase (MAPK) pathway [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPSR1 is a G-protein-coupled receptor that induces intracellular signaling upon stimulation by neuropeptide S (NPS) via mobilization of calcium, increased cyclic adenosine monophospate (cAMP) levels, and activation of the mitogen-activated protein kinase (MAPK) pathway [ 54 , 55 ]. Zhang et al [ 53 ] found that the expression level of NPSR1 in NSCLC was overexpressed. In addition, a previous study suggested that NPSR1 is a marker widely expressed in neuroendocrine tumors (NET) with the exception of adrenal pheochromocytomas, the stimulation of NPSR1 with NPS results in activation of pathways that are relevant for cancer development [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, bioinformatics analysis has become increasingly important for exploring underlying mechanisms of various cancers. 39–42 This study has established a transgenic mouse model of liver cancer (Alb-Cre/Myc mice), and Myc is suggested to be a proverbial oncogenic factor in HCC, 43 providing a potential target for the prognosis and treatment of HCC dependent on Myc variants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the 5-year endurance percentage of stage I NSCLC positive individuals receiving successful treatment may be up to maximum of 83%. So, early detection of NSCLC can decrease death ratio [1][2][3] . Prompt recognition of NSCLC on X-ray and sputum cytology has less sensitivity.…”
Section: Introductionmentioning
confidence: 99%